Increasing student literacy through reading corners at Nurul Ulum Primary School, Bojonegoro - Neneng Rika Jazilatul Kholidah; Chyntia Heru Woro Prastiwi; Rika Pristian Rika; Suhartono Suhartono (Community Empowerment, 2023)
Nurul Ulum Elementary School is a private institution with limited space, lacking a library or reading corner within the classrooms. Consequently, students have limited access to a diverse range of interesting books. This community service initiative aims to enhance student literacy by establishing a reading corner that offers various sources of reading material. The activities include setting up reading corners, conducting outreach, and performing evaluations. The outcome of these efforts is an increased interest among students in reading books and the development of literacy skills. This is evident through the enthusiasm of students who take turns selecting books and reading during break time. Through these initiatives, Nurul Ulum Elementary School students have successfully cultivated a culture of literacy within the school environment.